Marijuana dependence moderates the effect of posttraumatic stress disorder on trauma cue reactivity in substance dependent patients. (1st February 2016) - Tull, Matthew T.; McDermott, Michael J.; Gratz, Kim L.
Highlights: Examined moderating role of marijuana dependence on trauma cue reactivity in post traumatic stress disorder (PTSD). In absence of marijuana dependence, PTSD patients had more subjective reactivity. No differences in reactivity for marijuana dependent patients as a function of PTSD. Marijuana dependent PTSD patients less reactive than PTSD-no marijuana patients. Marijuana dependence may lead to a dampening of reactivity in patients with PTSD. Abstract: Background: Individuals with posttraumatic stress disorder (PTSD) are at heightened risk for marijuana use. Although extant studies speak to the importance of examining the co-occurrence of PTSD and marijuana use as it relates to a variety of clinically-relevant outcomes, no studies have explored the way in which marijuana use may affect in-the-moment emotional responding among individuals with PTSD. Thus, the purpose of this study was to explore the role of marijuana dependence in the relation between PTSD and subjective and biological emotional reactivity in response to a trauma cue. Methods: Participants were 202 patients with and without current PTSD consecutively admitted to a residential SUD treatment facility. Patients were administered diagnostic interviews, and subjective (negative affect) and biological (cortisol) reactivity to a personalized trauma cue were assessed. Results: Whereas current PTSD was associated with greater subjective emotional reactivity among participants without marijuana dependence, there were no significant differences in subjective emotional reactivity as a function of PTSD status among participants with marijuana dependence. Moreover, marijuana dependent participants (with and without PTSD) reported less subjective emotional reactivity than participants with PTSD and without marijuana dependence. No significant findings were obtained for cortisol reactivity. Conclusions: Findings suggest that patients with co-occurring PTSD and marijuana dependence may experience alterations in their emotional processing in response to a trauma cue (i.e., dampening of arousal). Additional research is required to clarify the specific mechanisms through which marijuana use influences emotional reactivity and fear-related emotional processing, as well as how such effects may influence PTSD treatment.